Health policies in Brazil: an analysis of projects financed by the World Bank during the Lula and Dilma governments - Lazarini, Welington Serra; Sodré, Francis; Sarti, Thiago Dias; Andrade, Maria Angélica Carvalho (Saúde e Sociedade, 2021)
The World Bank has been influencing the direction of the Brazilian National Health System over the last 30 years. This study analyzed the projects funded by the World Bank for the health sector in Brazil between 2003 and 2014. A documentary analysis was conducted on projects financed by the World Bank for the Brazilian health sector in the three government spheres, categorized according to content analysis. Of the 174 projects financed in the country, 31 contemplated the health sector in their composition, with 64.53% of these being signed with the state governments. Most of the health projects were signed in the second Lula government and the main structuring themes were: Human Development and Gender, Public Sector Management and Private Sector Development. The strategic displacement of the World Bank, which approached the state and municipal governments, was evident since the second administration of the Lula government. This movement denoted the World Bank’s ability to identify global changes in progress, especially regarding the geopolitical and economic scenario. The results show that the World Bank increased its interest in the Brazilian health sector and that the proposals contributed to boost the principles of state reform in the country